IMMIGRATION ADMINISTRATIVE ACTION LEGAL PORTRAIT - I Gusti Putu Anom Kresna; Ridha Nikmatus Syahada; M Azzam Alfarizi (Journal of Law and Border Protection, 2022)
The increasing era of globalization which causes traffic flow of people entering and leaving the territory of Indonesia. Selective Policy is one way to overcome the problem of traffic in people where this policy only allows foreign nationals who can provide benefits and do not interfere with state security who are allowed to enter Indonesian territory. To ensure that it is more effective, it is also necessary to implement a policy of providing appropriate Immigration Administrative Actions to suppress the increase in cases of immigration violations. This study, entitled Portrait of Immigration Administrative Action Law, will discuss the types of Immigration Administrative Actions and law enforcement efforts against immigration administrative actions. The purpose of this study was to determine the types and efforts of law enforcement against Immigration Administrative Actions. In this study using normative research methods because it is only aimed at written regulations so that this writing is very closely related to the library. This study explains that there are various types of Immigration Administrative Actions that are adapted to the types of violations committed by Foreign Citizens and the law enforcement efforts provided can be classified into two, namely in addition to being subject to Immigration Administrative Actions, immigration crimes can also be imposed to provide a deterrent effect to violators